Resource allocation over wireless relay network - Cai, William (2012)
This project is about developing a simulator based on the 802.16j standard to facilitate the evaluation the throughput resulting from the use of different bandwidth scheduling algorithms. The simulator would need to adhere to the standard as closely as possible to allow for a greater degree of accuracy in the results.